2017
DOI: 10.1038/gim.2016.163
|View full text |Cite
|
Sign up to set email alerts
|

Detection of clinically relevant copy-number variants by exome sequencing in a large cohort of genetic disorders

Abstract: Purpose:Copy-number variation is a common source of genomic variation and an important genetic cause of disease. Microarray-based analysis of copy-number variants (CNVs) has become a first-tier diagnostic test for patients with neurodevelopmental disorders, with a diagnostic yield of 10–20%. However, for most other genetic disorders, the role of CNVs is less clear and most diagnostic genetic studies are generally limited to the study of single-nucleotide variants (SNVs) and other small variants. With the intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
138
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(147 citation statements)
references
References 41 publications
6
138
2
1
Order By: Relevance
“…Indeed, recent studies showed that exonic CNVs play an important role in a broad range of genetic disorders, accounting for a considerable number of disease‐alleles (Gambin et al, ; Pfundt et al, ). In muscle disorders, intragenic deletions were found to represent about 6% of the disease‐variants (Pfundt et al, ). Therefore, this case indicates that the integrated CNVs and variants analysis could be offered also in prenatal diagnosis of selected cases.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies showed that exonic CNVs play an important role in a broad range of genetic disorders, accounting for a considerable number of disease‐alleles (Gambin et al, ; Pfundt et al, ). In muscle disorders, intragenic deletions were found to represent about 6% of the disease‐variants (Pfundt et al, ). Therefore, this case indicates that the integrated CNVs and variants analysis could be offered also in prenatal diagnosis of selected cases.…”
Section: Discussionmentioning
confidence: 99%
“…No relevant CNVs were detected in this DSD patient cohort, possibly due to the focus on coding regions. However, this research highlights the importance of investigating the role CNVs play in genetic disease and moves the field closer to a single genomics test [Pfundt et al, 2017]. Whole genome sequencing (WGS) has the potential to make all other techniques discussed in this review obsolete.…”
Section: Massively Parallel Sequencing Technologies: New Methods To Imentioning
confidence: 99%
“…Only within the last year has WES successfully been able to detect CNVs in other human disease studies with acceptable reliability [Gambin et al, 2016;Jo et al, 2016], although the precision of the data analysis pipelines is currently less than 80% when comparing large cohorts [Gambin et al, 2016]. Recently a study using WES to screen 2,603 patients with a range of genetic disorders, including 38 DSD patients, showed that on average each patient had 6 CNVs throughout their genome [Pfundt et al, 2017]. Across the entire patient cohort, WES successfully detected 123 clinically relevant CNVs with definitive diagnosis in 51 cases.…”
Section: Massively Parallel Sequencing Technologies: New Methods To Imentioning
confidence: 99%
“…10 Various strategies including biopsies, karyotype, chromosomal microarray analysis (CMA), Sanger sequencing, and multiplex ligationdependent probe amplification (MLPA) were developed to elucidate the molecular etiologies. 12 [14][15][16] However, to the best of our knowledge, studies of diagnostic yields using comprehensive detection of CNVseq and other NGS strategies are rarely reported. 11 In addition, only specific genes can be identified, while novel pathogenic genes cannot be detected.…”
Section: Introductionmentioning
confidence: 99%